Konseling Behavioral Teknik Self-Management untuk Meningkatkan Penyesuaian Diri pada Siswa - Permadin, Meiga latifah Putri; Marjo, Happy Karlina (Universitas Mathla'ul Anwar Banten, 2024)
The problem in this study is the lack of self-adjustment in first year students at public junior high schools. The purpose of this study was to determine the use of individual counseling with a behavioral approach to self-management techniques to improve self-adjustment in first-year students at state junior high schools. The experimental research design used in this study was Single Subject Research (SSR) with a single subject type (single subject design). The subjects of this study were two class VII students of SMP Negeri 2 Kelapa Dua. Data collection techniques used the Adjustment Inventory for School Students (AISS) instrument and interviews. The results showed that there was an increase in self-adjustment to students who were given individual counseling services using a behavioral approach to self-management techniques to improve self-adjustment in first-year students at state junior high schools. This is evidenced by the changes in the two subjects after the implementation of counseling. It can be concluded that individual counseling with a behavioral approach to self-management techniques is effective in improving self-adjustment in first-year students at public junior high schools.